2010
DOI: 10.1002/hfm.20210
|View full text |Cite
|
Sign up to set email alerts
|

Affective evaluation of user impressions using virtual product prototyping

Abstract: This study aims to develop an effective and efficient method of analyzing user impressions of a product using virtual prototyping. A method to analyze the relationship between user impressions and design elements of a product using virtual prototyping was proposed, and then the method was applied to the case study of automobile interior design. Thirty-two participants in the experiment evaluated 32 different virtual prototypes of automobile interiors generated from the combination of 17 design elements. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 26 publications
(37 reference statements)
3
11
0
2
Order By: Relevance
“…The results of the study indicated that the virtual prototype of the car is a close representative of its real model. This fact is in agreement with the previous literature [80,81].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of the study indicated that the virtual prototype of the car is a close representative of its real model. This fact is in agreement with the previous literature [80,81].…”
Section: Discussionsupporting
confidence: 94%
“…The results of the study indicated that the virtual prototype of the car is a close representative of its real model. This fact is in agreement with the previous literature [80]. This study provides the VP method for a complete car, which is not readily available in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…The instrument panel was chosen because drivers used it most frequently when they were in the car and the design of instrument panel has been evaluated for checking the interior styles of cars in terms of impressions, functionality, and usability (Cho & Lee, ; Shen, Chen, Liang, Pu, & Ma, ). Likewise, door‐trim armrest and A‐pillar were selected because they were not only frequently used by drivers but also they have been investigated as critical areas of automobile interior design (Kim, Lee, Lehto, & Yun, ; Soderberg, Lindkvist, & Carlson, ). In addition, instrument panel, door‐trim armrest, and A‐pillar are proper to apply illusory design elements because they are perceived as objects having multiple character lines and geometric shapes.…”
Section: Methodsmentioning
confidence: 99%
“…Affect is defined as consumers’ psychological responses to the perceptual design details of the product (Kim, Lee, Lehto, & Yun, ). Affect is essential for the formation of human values and human judgment (Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Affect is defined as consumers' psychological responses to the perceptual design details of the product (Kim, Lee, Lehto, & Yun, 2011).…”
Section: Introductionmentioning
confidence: 99%